Peculiarities of online user’s content search in the context of inbound marketing - Davidavičius, Sigitas (Business: Theory and Practice, 2024)
The article addresses the issue of the distribution of users browsing the internet for content in a specific format through alternative content delivery channels in the context of inbound marketing. The problem being addressed is part of a broader problem with the formation of traffic to an organization’s website. The theoretical part of the work presents the concept of inbound marketing and analyzes the theoretical aspects of its tactical activities, such as content marketing, search engine marketing, and social media marketing. Based on the theoretical research, the scientific hypothesis is formulated – there are links between the desired content format and the choice of content search and consumption channel. The research methodology consists of data collection by survey method and hypothesis testing using Cochran’s Q test. Empirical research has shown links between the content format sought and the channels for searching and consuming content. Although in almost all cases the search for video and audio content is dominated by search engines, evaluating other content delivery channels reveals a significant specialty of users’ web browsing.